Measuring access to medicines: a review of quantitative methods used in household surveys - Domingues Marlos R; Maia Maria; Fassa Anaclaudia G; Paniz Vera Maria V; Bertoldi Andréa D (BMC, 2010)
Abstract Background Medicine access is an important goal of medicine policy; however the evaluation of medicine access is a subject under conceptual and methodological development. The aim of this study was to describe quantitative methodologies to measure medicine access on household level, access expressed as paid or unpaid medicine acquisition. Methods Searches were carried out in electronic databases and health institutional sites; within references from retrieved papers and by contacting authors. Results Nine papers were located. The methodologies of the studies presented differences in the recall period, recruitment of subjects and medicine access characterization. Conclusions The standardization of medicine access indicators and the definition of appropriate recall periods are required to evaluate different medicines and access dimensions, improving studies comparison. Besides, specific keywords must be established to allow future literature reviews about this topic.